Long-term safety and efficacy of daclizumab beta in relapsing-remitting multiple sclerosis: 6-year results from the SELECTED open-label extension study - Gold, Ralf; Radue, Ernst-Wilhelm; Giovannoni, Gavin; Selmaj, Krzysztof; Havrdova, Eva Kubala; Montalban, Xavier; Stefoski, Dusan; Sprenger, Till; Robinson, Randy R; Fam, Sami; Smith, Jonathan; Chalkias, Spyros; et al. (Journal of neurology, 2020)
OBJECTIVE: SELECTED, an open-label extension study, evaluated daclizumab beta treatment for up to 6 years in participants with relapsing multiple sclerosis who completed the randomized SELECT/SELECTION studies. We report final results of SELECTED. METHODS: Eligible participants who completed 1-2 years of daclizumab beta treatment in SELECT/SELECTION received daclizumab beta 150 mg subcutaneously every 4 weeks for up to 6 years in SELECTED. Safety assessments were evaluated for the SELECTED treatment period; efficacy data were evaluated from first dose of daclizumab beta in SELECT/SELECTION. RESULTS: Ninety percent (410/455) of participants who completed treatment in SELECTION enrolled in SELECTED. Within SELECTED, 69% of participants received daclizumab beta for > 3 years, 39% for > 4 years, and 9% for > 5 years; 87% of participants experienced an adverse event and 26% a serious adverse event (excluding multiple sclerosis relapse). No deaths occurred. Overall, hepatic events were reported in 25% of participants; serious hepatic events in 2%. There were no confirmed cases of immune-mediated encephalitis. Based on weeks from the first daclizumab beta dose in SELECT/SELECTION, adjusted annualized relapse rate (95% confidence interval) for weeks 0-24 was 0.21 (0.16-0.29) and remained low on continued treatment. Overall incidence of 24-week confirmed disability progression was 17.4%. Mean numbers of new/newly enlarging T2 hyperintense lesions remained low; percentage change in whole brain volume decreased over time. CONCLUSIONS: The effects of daclizumab beta on clinical and radiologic outcomes were sustained for up to ~ 8 years of treatment. No new safety concerns were identified in SELECTED. TRIAL REGISTRATION: Clinicaltrials.gov NCT01051349; first registered on January 15, 2010.
Keywords: dospělí; Immunoglobulin G; relabující-remitující roztroušená skleróza; imunosupresiva; Humans; mužské pohlaví; daklizumab; humanizované monoklonální protilátky; Adult; Multiple Sclerosis, Relapsing-Remitting; Antibodies, Monoclonal, Humanized; roztroušená skleróza; Multiple Sclerosis; imunoglobulin G; ženské pohlaví; Immunosuppressive Agents; lidé; Daclizumab; Male; Female